Analisis Sistem Informasi Akuntansi Berdasarkan ISAK 35 Pada Organisasi Nonlaba (Studi Kasus Pada Paroki Hati Yesus Yang Mahakudus Ili) - Brigitha Laura; Wilhelmina Mitan; Siktania Maria Dilliana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the application of information systems for the Parish of the Most Holy Ili Heart of Jesus based on the applicable Interpretation of Financial Accounting Standards (ISAK) 35. The design of this study is descriptive qualitative with data collection techniques in the form of observation, documentation and interviews. The type of data in this study is a type of qualitative data with primary data sources and secondary data sources. Data analysis in this study was in the form of data collection, data reduction, data display and verification. The results of this study indicate that the accounting information system applied to Ili's Sacred Heart of Jesus Parish has met several accounting information system indicators, namely human resources, equipment, forms and records. However, procedures and reports are still not in accordance with the accounting information system indicators. The accounting information system at Ili's Most Holy Heart of Jesus Parish also has not produced complete financial reports, only in the form of profit and loss statements and balance sheets and is not in accordance with the provisions of the ISAK 35 standard.